A Parametric Study of Low Wind Speed Enhancement System - Chew, Weiee (2015)
A research study on a low wind speed enhancement system in Malaysia. The system is used to harness wind energy from all direction to generate electricity through a wind turbine. The objective of this research is to study the low wind speed enhancement system with different geometry parameter and optimize the performance of the design. There are 2 software that used in this research which is Autodesk Inventor and ANSYS Fluent. Besides that, there are total 4 system design and 4 research on the chapter 4 results and discussion. A series of parametric simulation has been done in this research to optimize the performance of the system. The wind speed at the nozzle has increase from the first design 2mIs to the final design 5.7m/s which is 96.1% in different.